2018
DOI: 10.1186/s13045-018-0680-7
|View full text |Cite
|
Sign up to set email alerts
|

A potent immunomodulatory role of exosomes derived from mesenchymal stromal cells in preventing cGVHD

Abstract: BackgroundMesenchymal stromal cells (MSCs) are a promising therapy for preventing chronic Graft-Versus-Host Disease (cGVHD) due to their potent immunomodulatory properties. However, the safety concerns regarding the use of MSCs remain unsolved, and conflicting effects are observed due to the heterogeneity of MSCs. Recently, exosomes were shown to mediate the paracrine effects of MSCs, making it a potential candidate for cell-free therapies. The aim of this study is to investigate the efficacy and safety of MSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
128
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(134 citation statements)
references
References 44 publications
6
128
0
Order By: Relevance
“…Therapeutic effects of MSC-derived exosomes in liver, kidney, cardiovascular, and neurological diseases functional MHC-peptide complexes to modulate tumor-specific T cell activation [54]. Exosomes released from Bone marrow (BM)-derived MSCs can effectively ameliorate chronic graft-versus-host disease (cGVHD) in mice by inhibiting the activation and infiltration of CD4 T cells, reducing pro-inflammatory cytokine production, as well as improving the generation of IL-10-expressing Treg and inhibiting Th17 cells [55]. Human multipotent stromal cells-derived EVs suppress autoimmunity in models of type 1 diabetes (T1D) and experimental autoimmune uveoretinitis (EAU).…”
Section: Neurological Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic effects of MSC-derived exosomes in liver, kidney, cardiovascular, and neurological diseases functional MHC-peptide complexes to modulate tumor-specific T cell activation [54]. Exosomes released from Bone marrow (BM)-derived MSCs can effectively ameliorate chronic graft-versus-host disease (cGVHD) in mice by inhibiting the activation and infiltration of CD4 T cells, reducing pro-inflammatory cytokine production, as well as improving the generation of IL-10-expressing Treg and inhibiting Th17 cells [55]. Human multipotent stromal cells-derived EVs suppress autoimmunity in models of type 1 diabetes (T1D) and experimental autoimmune uveoretinitis (EAU).…”
Section: Neurological Diseasementioning
confidence: 99%
“…Improved preclinical study quality in terms of treatment allocation reporting, randomization and blinding will accelerate needed progress towards clinical trials that should assess the feasibility and safety of this therapeutic approach in humans [61]. For example, MSC-exosomes will be great adipose derived-MSCs hepatitis TNF-α, IFN-γ, IL-6, IL-18 and IL-1β [33] human umbilical cord-derived MSCs renal Ischemia-reperfusion injury (IRI) VEGF [34] adipose tissue-derived autologous MSCs renal artery stenosis TNF-α, IL-6, IL10 and IL-1-β [35] human bone marrow MSCs acute kidney injury mRNAs [36] bone marrow MSCs acute renal injury Bcl-xL,Bcl2, BIRC8,Casp1, Casp8 and LTA [37] human umbilical cord MSCs unilateral renal ischemia lipocalin [38] bone marrow MSCs acute kidney injury mRNAs [36] Human bone marrow MSCs damaged renal tubular IGF-1R [39] adipose-derived MSC myocardial ischemia-reperfusion injury Wnt/β-catenin [41] endometrium-derived MSCs myocardial infarction miR-21, PTEN [42] HuES9.E1 derived MSCs myocardial ischemia/reperfusion injury PI3K/Akt [43] mouse bone marrow-derived MSCs myocardial infarction miR-22, Mecp2 [44] bone marrow MSCs myocardial infarction miR-125b [45] human mesenchymal stem cell cardiac contractility miR-21-5p, PI3K [46] bone marrow-derived MSCs myocardial ischaemia reperfusion injury AMPK/mTOR, Akt/mTOR [47] rat bone marrow derived MSCs stroke miR-17-92, PTEN [50] human adipose tissue-derived MSCs Alzheimer's disease neprilysin [51] adipose-derived stem cells oxygen-glucose deprivation MicroRNA-181b/TRPM7 [52] mouse bone marrow MSCs Alzheimer's disease STAT3, NF-κB [ 53] bone marrow derived MSCs chronic graft-versus-host disease Treg, Th17 [55] human multipotent stromal cells type 1 diabetes, uveoretinitis Th1, Th17 [56] human bone-marrow derived MSCs asthma IL-10, TGF-β1 [ 57] human umbilical cord MSCs inflammation MiR-181c, TLR4 [58] biological tools for cancer therapy, it is hopeful to delve deeper into the potential of MSC-exosomes among cancer cells and provide effective treatments with the highest safety [62] Table 2.…”
Section: Clinical Trials Of Mscs Exosomes-based Therapiesmentioning
confidence: 99%
“…The positive effect of exosomes is amply documented in several pathologies: Lai et al in 2018 suggested that MSC-derived exosomes could improve graft versus host disease in mice through the inhibition of CD4 T cells [24]. In addition, the exosomes exhibit immune-modulatory properties by activating the regulatory T cells and blocking Th17 cells; Cui et al in 2018 concluded that adipose-derived MSCs (ADMSCs) exosomes were able to rescue ischemic myocardium from ischemia/reperfusion damage by the action of their anti-apoptotic and pro-survival properties on cardiomyocytic cells.…”
Section: Stem Cell-derived Exosomes As Tool For Cell-free Therapymentioning
confidence: 99%
“…In 2010, the therapeutic potential of MSC-derived EVs was tested in a mouse model of ischemia (Lai et al, 2010 ). Since then, EVs have been investigated in several other disease models, such as cardiovascular disorders (Wang N. et al, 2017 ), kidney injury (Aghajani Nargesi et al, 2017 ; Farzamfar et al, 2019 ), immune diseases (Lai et al, 2018 , 2019 ), tumor growth (Wu et al, 2013 ; Zhang et al, 2017 ) and neurological diseases (Wang et al, 2018 ; Gorabi et al, 2019 ), obtaining encouraging results (Yu et al, 2014 ).…”
Section: Cellular-free Approachesmentioning
confidence: 99%